2013
DOI: 10.1097/scs.0b013e31828a7c4c
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Melanotic Neuroectodermal Tumor of Infancy Management

Abstract: Melanotic neuroectodermal tumor of infancy (MNTI), an uncommon neoplasm that involves predominantly the maxilla, is classically benign but clinically aggressive. Surgery is the mainstay of the treatment with a proven efficacy, but its optimal method is not entirely clear. A case of maxillary MNTI in a 4-month-old male infant treated by radical surgery without recurrence after more than 3 years of follow-up is presented. On the basis of this experience and a review of the literature, the optimal method of MNTI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[17][18][19] Further, our literature review demonstrated that 92.5% of tumors affected the maxilla and 7.5% affected the mandible. 3,11,16,22 In our analysis, five cases reported regional lymph node metastasis and two were confirmed to be affected by the lesion. The melanotic epithelioid cells generally surround nests of small cells but may form solid and tubuloglandular structures.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…[17][18][19] Further, our literature review demonstrated that 92.5% of tumors affected the maxilla and 7.5% affected the mandible. 3,11,16,22 In our analysis, five cases reported regional lymph node metastasis and two were confirmed to be affected by the lesion. The melanotic epithelioid cells generally surround nests of small cells but may form solid and tubuloglandular structures.…”
Section: Discussionmentioning
confidence: 56%
“…11,14,21 We observed that radical surgery is the best treatment approach, consistent with other previous studies. 3,11,16,22 In our analysis, five cases reported regional lymph node metastasis and two were confirmed to be affected by the lesion. MNTI of the jaw bones has not previously been described as presenting an association with regional lymph node metastasis.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…2 The recurrent tumors grow more aggressively and can invade other anatomic structures, such as the nasal cavity, the orbit, and the skull base. 4 The Raf-MEK-ERK mitogen-activated protein kinase pathway is activated by growth factors, hormones, and cytokines and regulates proliferation, differentiation, survival, senescence, and migration of cells. 5 Among other isoforms of the Raf serine/threonine kinases, B-Raf (encoded by the BRAF gene) has a dominant role in signaling to the ERK pathway.…”
Section: Introductionmentioning
confidence: 99%